2021
DOI: 10.1055/a-1673-1765
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Maternal Abdominal Surface Electrode System for Fetal Heart Rate and Uterine Contraction Monitoring from 34 to 37 Weeks

Abstract: Objective: Compare performance of a maternal surface electrode patch with ultrasound- and tocodynamometer-based monitoring to detect fetal heart rate and uterine contractility in late preterm labors. Study design: Thirty women between 340/7 and 366/7 weeks’ gestation were monitored simultaneously with a Doppler/tocodynamometer system and a wireless fetal-maternal abdominal surface electrode system. Fetal and maternal heart rate and uterine contraction data from both systems were compared. Reliability was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It is important that the performance of the NI‐FECG device is high in both preterm and term monitoring, as prolonged FHR monitoring can be used throughout pregnancy to detect clinical deterioration. Reliable and accurate performance of NI‐FECG devices for MHR measurements has been reported previously 19,23 . Previous research has shown that women prefer the comfort of the NI‐FECG device over the DU device 18,26 .…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…It is important that the performance of the NI‐FECG device is high in both preterm and term monitoring, as prolonged FHR monitoring can be used throughout pregnancy to detect clinical deterioration. Reliable and accurate performance of NI‐FECG devices for MHR measurements has been reported previously 19,23 . Previous research has shown that women prefer the comfort of the NI‐FECG device over the DU device 18,26 .…”
Section: Discussionmentioning
confidence: 82%
“…Monica-AN24, 17,20,21,25,26 Monica-Novii 18,19 and Nemo. 23,24 Other commercial NI-FECG devices known to the authors are: Fetal Lite and Meridian-M110.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations